An Investigation into Iraqi EFL University Students’ Difficulties in Writing English Compositions - Fadhala, Ali Kareem (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research examined the challenges encountered by Iraqi EFL students in composing written texts in English. The objective was to pinpoint the particular aspects where Iraqi EFL students experience difficulties, including grammar, vocabulary, organization, and content development. A mixed-methods approach was adopted for this study, incorporating both quantitative and qualitative data collection methods. Written compositions from a cohort of 42 Iraqi EFL university students at the College of Education, AL-Shatrah University were subjected to error analysis and thematic evaluation. Furthermore, questionnaires and interviews were administered to collect insights regarding students' views on their writing challenges and the underlying factors that contribute to these issues. The research indicates that Iraqi EFL students face various challenges, such as incorrect grammar application, restricted vocabulary, inadequate organization of their thoughts, and struggles in producing and elaborating coherent content. Additionally, the study investigated the possible reasons behind these challenges, taking into account factors like the influence of the students' first language, lack of writing practice, minimal exposure to English, and insufficient teaching of writing techniques. The findings underscore the necessity for focused interventions and teaching methods to tackle the particular writing challenges faced by Iraqi EFL students, with the goal of enhancing their writing skills and overall communicative effectiveness.